Factors influencing the food preferences of South Indian youngsters - M.P , Nepoleon (The journal of contemporary issues in business and government, 2021)
Food choice is influenced by many interacting factors in humans. The study aimed at determining the food choices, preferences and eating behavior among the young south Indian adults that are affected by some factors such as health, mood, economic, convenience, sensory, natural content, weight control and familiarity. India is the country were the diversity plays huge role among the factors of decision making. There are five states and one union territory in south India. The study also aimed to look at the deviation in the preferences of food choices of the South Indian youngsters based on their region. The data collected through online survey using Google forms that had been spread through various regions in south India and captured 150 responses from the youngsters within the age group of 16 to 35. The analysis is focused on the food choices of the youngsters based on the region and gender, how they vary according to the impact of the factors that taken in the study.